Vedolizumab in patients with concurrent primary sclerosing cholangitis and inflammatory bowel disease does not improve liver biochemistry but is safe and effective for the bowel disease. Issue 6 (29th January 2018) - Christensen, B.; Micic, D.; Gibson, P. R.; Yarur, A.; Bellaguarda, E.; Corsello, P.; Gaetano, J. N.; Kinnucan, J.; Rao, V. L.; Reddy, S.; Singh, S.; Pekow, J.; et al.
Summary: Background: Blocking of lymphocyte trafficking to bile ducts is a potential mechanism to alter the disease course of patients with primary sclerosing cholangitis (PSC). Aim: To describe the effect of the α4 β7 integrin antibody, vedolizumab, on liver biochemistry and disease activity in patients with PSC and inflammatory bowel disease (IBD). Methods: This is a retrospective multi‐centre study of adult patients with a diagnosis of both IBD and PSC. The primary outcome was change in serum alkaline phosphatase level at weeks 14 and 30. Secondary outcomes included changes in other liver biochemistries and in clinical outcomes for the bowel disease. A safety analysis for adverse events was performed. Results: Thirty‐four patients (16 Crohn's disease, 18 ulcerative colitis) were included. Nine (26%) had a history of liver transplant. Median follow‐up on vedolizumab was 9 months (IQR: 7‐16). There was no overall change in serum alkaline phosphatase level with vedolizumab therapy (median 268 [IQR: 105‐551] IU/L at baseline versus 249 [IQR: 183‐634] IU/L, P = 0.99 at week 30). No significant changes in other liver biochemistries or the Mayo PSC Risk Score were demonstrated at week 30. Clinical remission was achieved at week 30 in 55% of Crohn's disease and 29% of ulcerative colitis patients. Seven (21%) patients ceased vedolizumab; six patients stopped therapy due to persistent IBD activity and one for worsening of liver biochemistries. Conclusion: Vedolizumab treatment in patients with PSC and IBD did not improve liver biochemistry but was associated with improvement in bowel disease and a favourable safety profile. Abstract : Linked Content This article is linked to Pavlidis et al and Christensen et al papers. To view these articles visit https://doi.org/10.1111/apt.14603 and https://doi.org/10.1111/apt.14638 .